TORC1 and class I HDAC inhibitors synergize to suppress mature B cell neoplasms. Issue 2 (3rd December 2013) - Simmons, John K.; Patel, Jyoti; Michalowski, Aleksandra; Zhang, Shuling; Wei, Bih-Rong; Sullivan, Patrick; Gamache, Ben; Felsenstein, Kenneth; Kuehl, W. Michael; Simpson, R. Mark; Zingone, Adriana; Landgren, Ola; et al.
Abstract : Enhanced proliferative signaling and loss of cell cycle regulation are essential for cancer progression. Increased mitogenic signaling through activation of the mTOR pathway, coupled with deregulation of the Cyclin D/retinoblastoma (Rb) pathway is a common feature of lymphoid malignancies, including plasmacytoma (PCT), multiple myeloma (MM), Burkitt's lymphoma (BL), and mantle cell lymphoma (MCL). Here we evaluate the synergy of pharmacologically affecting both of these critical pathways using the mTOR inhibitor sirolimus and the histone deacetylase inhibitor entinostat. A dose‐matrix screening approach found this combination to be highly active and synergistic in a panel of genetically diverse human MM cell lines. Synergy and activity was observed in mouse PCT and human BL and MCL cell lines tested in vitro, as well as in freshly isolated primary MM patient samples tested ex vivo. This combination had minimal effects on healthy donor cells and retained activity when tested in a co‐culture system simulating the protective interaction of cancer cells with the tumor microenvironment. Combining sirolimus with entinostat enhanced cell cycle arrest and apoptosis. At the molecular level, entinostat increased the expression of cell cycle negative regulators including CDKN1A (p21) and CDKN2A (p16), while the combination decreased critical growth and survival effectors including Cyclin D, BCL‐XL, BIRC5, and activated MAPK. Highlights: Entinostat combined with sirolimus synergistically inhibits B cell neoplasms. Combination treatment limits growth of xenografts and cells from myeloma patients. Combination treatment is effective in the presence of stromal cells. Combination treatment enhances apoptosis and cell cycle arrest. Combination treatment enhances MAPK inhibition over single agent use.